The value of publishing in JIBS - Li, Chengguang; Ahn, Jungsoo; Bu, Juan; Meyer, Klaus E. (Journal of International Business Studies, 2023)
Young management scholars often wonder to what extent they should emphasize international business scholarship in their career. In this commentary, we argue that, in addition to its intellectual merits, publishing in the leading outlet in the field, Journal of International Business Studies (JIBS), also pays financially on a par with publishing in other top management journals. Our claim is based on an analysis of the impact of JIBS publications on a strategy faculty’s nine-month salary for a sample of 396 strategy professors from the business schools of 59 research-oriented US public universities from 2015 to 2019. Employing multilevel modeling, we find that publishing in JIBS significantly increases faculty’s annual salary by, on average, more than US$3,000, which is equivalent to the salary gains for publishing in leading general management and strategy journals. Thus, the recognition of JIBS is on par with that of other top management journals, and IB as a field of study is a financially rewarding career path. Moreover, JIBS may offer a blueprint for other business and management journals to build reputation by continuously publishing papers with high standards that continuously develop insights and theory relevant to contemporary business.